The Drivers of Long-run CO2 Emissions: A Global Perspective since 1800 - Sofia Teives Henriques; Karol J. Borowiecki (European Historical Economics Society (EHES), 2014)
Fossil-fuel-related carbon dioxide emissions have risen dramatically since 1800. We identify the long-run drivers of CO2 emissions for a sample of twelve developed economies using an extended Kaya decomposition. By considering biomass and carbon-free energy sources along with fossil fuels we are able to shed light on the effects of past and present energy transitions on CO2 emissions. We find that at low levels of income per capita, fuel switching from biomass to fossil fuels is the main contributing factor to emission growth. Scale effects, especially income effects, become the most important emission drivers at higher levels of income and also dominate the overall long-run change. Technological change is the main offsetting factor. Particularly in the last decades, technological change and fuel switching have become important contributors to the decrease in emissions in Europe. Our results also individualize the different CO2 historical paths across parts of Europe, North America and Japan.
Keywords: N70; O44; Q40; Q54; Q5; 330; CO2 emissions; Kaya decomposition; Energy transition